Inside Cover: Rescue of Functional CFTR Channels in Cystic Fibrosis: A Dramatic Multivalent Effect Using Iminosugar Cluster‐Based Correctors (ChemBioChem 15/2013). Issue 15 (7th October 2013) - Compain, Philippe; Decroocq, Camille; Joosten, Antoine; de Sousa, Julien; Rodríguez‐Lucena, David; Butters, Terry D.; Bertrand, Johanna; Clément, Romain; Boinot, Clément; Becq, Frédéric; Norez, Caroline
<x xml:space="preserve">Abstract</x> The inside cover picture shows a trivalent iminosugar as a powerful trident to target cystic fibrosis by rescuing mutant CFTR channels. This compound, displaying three copies of the clinical candidate miglustat, leads to a CFTR corrector that is superior by two orders of magnitude in efficiency. For more details, see the paper by P. Compain et al. on p. 2050 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>